The elusive “indieness": Measuring the defining characteristics of indie games - Pereira, Leônidas Soares (Loading)

(untitled) (Canadian Game Studies Association, 2021)
This article aims to investigate what are the internal and external marking traits of indie games. Building up on previous efforts from other scholars, we developed a mix method research approach relying on interviews with indie game developers and a quantitative survey. Rather than trying to “re-invent the wheel” by proposing a new definition for the term, we attempt to map out what are the significant distinctive factors present in contemporary indie game from the perspective of developers and non-developers alike, while also discussing the changes of meaning it might have been subject to over time. We found that the determiningtraits of what allows one to perceive a game as indie change over time,andthat,despite thecorefact thatcreative independence remainsthe central feature of all indie games, the conditions for achieving this independence appear to be rather flexible, especially when it comes to issues of funding and publishing agreements. Additionally, our findings point to the term "indie" as being highly mutable and reliant on temporal and contextual aspects, with the qualities that divideindie fromnon-indie games being more akin to a continuum than something rigidly binary.